2017
DOI: 10.1142/s0129065717500290
|View full text |Cite
|
Sign up to set email alerts
|

Automated Detector of High Frequency Oscillations in Epilepsy Based on Maximum Distributed Peak Points

Abstract: High frequency oscillations (HFOs) are considered as biomarker for epileptogenicity. Reliable automation of HFOs detection is necessary for rapid and objective analysis, and is determined by accurate computation of the baseline. Although most existing automated detectors measure baseline accurately in channels with rare HFOs, they lose accuracy in channels with frequent HFOs. Here, we proposed a novel algorithm using the maximum distributed peak points method to improve baseline determination accuracy in chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 59 publications
0
54
0
Order By: Relevance
“…However, the use of such standard configurations leads to suboptimal performance when used for a different data set or frequency range. For example, when previously published algorithms are implemented without optimizing the parameters, they exhibit lower detection accuracy (relative to visually detected events) than originally reported (Gardner et al 2007;Dümpelmann et al 2012;Cimbálník et al 2018;Ren et al 2018). Consistent with this, several studies have demonstrated that HFO detection accuracy relative to visually marked events can be improved by optimizing the algorithm parameters (Zelmann et al 2012;Chaibi et al 2013;Charupanit and Lopour 2017).…”
Section: Introductionmentioning
confidence: 67%
“…However, the use of such standard configurations leads to suboptimal performance when used for a different data set or frequency range. For example, when previously published algorithms are implemented without optimizing the parameters, they exhibit lower detection accuracy (relative to visually detected events) than originally reported (Gardner et al 2007;Dümpelmann et al 2012;Cimbálník et al 2018;Ren et al 2018). Consistent with this, several studies have demonstrated that HFO detection accuracy relative to visually marked events can be improved by optimizing the algorithm parameters (Zelmann et al 2012;Chaibi et al 2013;Charupanit and Lopour 2017).…”
Section: Introductionmentioning
confidence: 67%
“…In order to detect HFOs, we selected five minute segments during slow sleep period in which the delta band measured higher than 25% of all delta bands in a 30 second epoch. We also refer to the results of electrooculography and chin electromyography in determining the slow wave sleep period ( 10 ). All segments were selected from interictal periods, separated at least 2 h from seizures, and were transformed to a bipolar montage made of adjacent contacts.…”
Section: Methodsmentioning
confidence: 99%
“…Over the past two decades, numerous studies have shown that the removal of areas showing high rates of high frequency oscillations (HFOs) is associated with a good-surgical outcome ( 4 8 ). Therefore, HFOs are considered a promising biomarker of the seizure onset zone (SOZ) or epileptogenic zone ( 4 , 9 , 10 ). However, none of these studies have applied the quantitative threshold of HFO distribution to delineate the EZ.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations